(DPEPhos)Ni(mesityl)Br: An Air-Stable Pre-Catalyst for Challenging Suzuki–Miyaura Cross-Couplings Leading to Unsymmetrical Biheteroaryls - Sawatzky, Ryan S.; Stradiotto, Mark (Synlett, 2018)
The successful application of (DPEPhos)Ni(mesityl)Br (C1) as a pre-catalyst in the Suzuki–Miyaura cross-coupling of heteroaryl chlorides or bromides and heteroaryl boronic acids is reported. The use of C1 in this context allows for such reactions to be conducted under mild conditions (2 mol% Ni, 25 °C), including cross-couplings leading to unsymmetrical biheteroaryls. Successful transformations of this type involving problematic pyridinyl boronic acid substrates (10 mol% Ni, 60 °C) are also described.
Keywords: Suzuki–Miyaura; nickel; biheteroaryls; heteroaryl boronic acids; heteroaryl halides